Acceleration of Convergence of the Alternating Least Squares Algorithm for Nonlinear Principal Components Analysis - Kuroda, Masahiro; Mori, Yuichi; Iizuka, Masaya; Sakakihara, Michio (IntechOpen, 2012)
None